2015
DOI: 10.1111/1749-4877.12102
|View full text |Cite
|
Sign up to set email alerts
|

Frequent and prolonged nocturnal occupation of port areas by Yangtze finless porpoises (Neophocaena asiaeorientalis): Forced choice for feeding?

Abstract: During the Yangtze Freshwater Dolphin Expedition 2012, Yangtze finless porpoises (Neophocaena asiaeorientalis) were acoustically monitored in 9 port areas at night. During 6566 min of nocturnal monitoring, porpoise sonar was detected for 488 min (7.43% of the total time). Of all 81 encounters, the longest echolocation span obtained was 102.9 min, suggesting frequent and prolonged porpoise occupation of the port areas. A combined total of 2091 click trains were recorded, with 129 (6.2%) containing minimum inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 34 publications
(56 reference statements)
2
48
0
Order By: Relevance
“…Furthermore, fewer dolphins were detected within an area with fewer fish choruses, despite the significantly lower vessel presence. Previous studies on Yangtze finless porpoises have also reported high detection rates in areas where vessel, but also fish activity, was greater (Kimura et al 2012, Wang et al 2014, 2015a); for which forced-feeding was the offered explanation (Wang et al 2014(Wang et al , 2015a. While the findings within the current study may suggest Indo-Pacific humpback dolphins might be demonstrating a degree of tolerance for vessels due to foraging pressure, more data are needed to strengthen such an argument for Indo-Pacific humpback dolphins within the current study.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Furthermore, fewer dolphins were detected within an area with fewer fish choruses, despite the significantly lower vessel presence. Previous studies on Yangtze finless porpoises have also reported high detection rates in areas where vessel, but also fish activity, was greater (Kimura et al 2012, Wang et al 2014, 2015a); for which forced-feeding was the offered explanation (Wang et al 2014(Wang et al , 2015a. While the findings within the current study may suggest Indo-Pacific humpback dolphins might be demonstrating a degree of tolerance for vessels due to foraging pressure, more data are needed to strengthen such an argument for Indo-Pacific humpback dolphins within the current study.…”
Section: Discussionsupporting
confidence: 48%
“…, ); for which forced‐feeding was the offered explanation (Wang et al . , ). While the findings within the current study may suggest Indo‐Pacific humpback dolphins might be demonstrating a degree of tolerance for vessels due to foraging pressure, more data are needed to strengthen such an argument for Indo‐Pacific humpback dolphins within the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), as has the tendency of porpoises to forage within port environments, where they also display boat avoidance behavior (Wang et al . ). These facts together suggest that Yangtze finless porpoises experience food shortages in Yangtze River, and that they are forced to forage in unfavorable environments (Wang et al .…”
Section: Yangtze Finless Porpoise Specimen Datamentioning
confidence: 97%
“…These facts together suggest that Yangtze finless porpoises experience food shortages in Yangtze River, and that they are forced to forage in unfavorable environments (Wang et al . ). However, the diet of the Yangtze finless porpoise has been poorly known for a long time because of the lack of studies of stomach contents.…”
Section: Yangtze Finless Porpoise Specimen Datamentioning
confidence: 97%